Mathematical Model of Communication of Multiple Simulators in an Environment Based on the HLA Standard - Krzysztof PANUFNIK; Tadeusz NOWICKI (Communications of International Proceedings, 2024)
The paper presents a mathematical model of the communication process of simulators connected in the HLA architecture (high-level architecture). Simulators connected in this architecture, called federates, often use common data, the values of which can change. Information about changes is sent to other federates interested in these changes. The problem of choosing a method of notifying other federates about the changes that have occurred arises. Communication usually places a heavy burden on the network with federates. The motivation for this work was to develop a strategy for broadcasting information about changes that causes the lowest communication load in the network. There are few methods presented in the literature that address this problem. Moreover, they are not effective enough. The paper presents a mathematical (stochastic) model of communication processes between federates and criteria for assessing the efficiency and effectiveness of these processes. The next step will be to develop a simulation model and experimental research methodology for assessing the effectiveness of communication control methods in the HLA architecture.
Keywords: Simulation; standard HLA; data distribution service; data communication management.